PERANAN DAN FUNGI WANITA DALAM INDUSTRI LOGAM RADISIONAL DI YOGYAKARTA DAN JAWA TENGAH : STUDI ETNOARKEOLOGI - Djoko Dwiyanto; J. Susetyo Edy Yuwono (Humaniora, 1999)
The research studies the role and function of woman labor in traditional metal ind stries. The industries used to be assumed as a field that was dominated by man 1 bor. Although socio-culturally women h ve some obstacles and absenteeism in orking in the industries, in fact women a so have a role in economic activities as a hole. To prove the assumption the study is conducted on metal industry sector in order to know whether there are chances for omen to get higher and to develop their tier in that field to increase woman's inome. The research problem is approached ased on the perception and attitude of t aditional society on employment woman 1 bor in a certain position in industrial sector or another sector as a comparison aproach